The influence of assistance to birth in the postpartum outcomes (Research, Society and Development, 2020)
The objective of this study is to describe the postpartum outcomes that are influenced by the type of birth assistance. It was realized by a descriptive, retrospective, documental and quantitative research that analyzed 1062 medical records of women that gave birth between June 2018 and May 2019 in a low risk maternity in the countryside of Rio Grande do Sul. The analysis was done by qui square test being significative the values less then 5%. Predominated the horizontal birth positions being the vertical birth position more associated to the nurse’s conduct. The use of induction was correlated to a longer time of expulsion stage and the occurring of tears and was not associated to complications. Although the type of birth was associated to complications. This study concludes that the induction of birth influenced in the frequency of tears unlike the birth position that was not associated.